Integrating Character Values in Junior Secondary Student Writing Learning - Fadly Akbar; Sulkifli Sulkifli (P3I Luwu Raya, 2021)
This study aims to determine the integration of character values in junior high school students' writing learning. This research is a descriptive study. The subjects of this study were 35 grade VII students. The data was collected using test results of learning and observation results. The collected data were analyzed using qualitative analysis. The results of the qualitative analysis show the integration of the values of character education, namely the values of responsibility, discipline, honesty, self-confidence, courtesy, hard work, cooperation, respect, meticulousness and meticulousness, which are embedded in the learning of Indonesian for Class VII students of SMP Negeri 2. Bulukumba.